Impact of Acid, Alkali and Microbial Hydrolysis on Bioethanol Yield from Peels of Cassava, Yam and Potato Sourced From Food Vendors in Etsako West Local Government Area, Edo State, Nigeria - U. J. Ovueni; D. V. Adegunloye; A. K. Onifade (Journal of Applied Sciences and Environmental Management)
This study evaluated the impact of acid, alkali, and microbial hydrolysis on ethanol yield from cassava, yam, and potato peels. Samples were sourced locally in Etsako West (LGA), Edo State, Nigeria using appropriate standard procedures. The RSM revealed that ethanol yield decreased with rising fermentation temperature but increased with substrate concentration and fermentation time. Optimal conditions were 14% substrate concentration, 34°C, and 55 hours of fermentation. Acid hydrolysates yielded the highest ethanol (0.22–0.27 mL/g), followed by alkali (0.21–0.25 mL/g) and microbial hydrolysates (0.14–0.20 mL/g). CPP acid hydrolysate achieved the highest fermentation efficiency (59.11%), followed by alkali (48.19%) and microbial (41.84%). ANOVA confirmed significant differences between hydrolysis methods, with acid and alkali methods yielding comparable results. While some ethanol quality parameters aligned with commercial standards, others varied significantly. Acid hydrolysis proved most effective, highlighting its potential for optimizing ethanol production from agricultural waste.